EFFICIENT IMPLEMENTATION OF PLATFORM AS A SRVICE USING ANDROID BASED CLOLD SERVER” - , Prof. P. L. R, Ms. Bhagyashri D. Patil (International Journal of Scientific Research and Management (IJSRM), 2014)
Thenumber of Smartphone user sand mobile application sare growing rapidly.Though smart phone sare expected to have PC like functionality, hardware resources such as CPUs, memory and batterie sare stilllimited. To solve this resource problem, many researches have proposed architectures to use server resources in the cloud for mobile devices. The system proposed conceptual architecture of development of android cloud for efficient implementation of platform as a service, which enables multiple user Android applications on cloud server via network. Though Androidis mainly designed for physical Smartphone, Android’s to other feature sare useful to constructa server platform. Android is open-source product and run so nanx86 CPU. Android isanopen-source mobileOS initiated by Google. The main reason to use Android as a server platform is that it is able to run not only for smart phones but also for the x86 platform include in gservers. We show three types of multitenant architecture for an Android server platform and discuss the direction to take toitreality.